Optimisation of image quality and radiation dose using air-gap technique in pelvic radiography - Moey, Soo Foon; Mohd Rosli, Mariyya; Sayed, Inayatullah Shah (Research Publish Journals, 2016)
The aim of the study was to investigate the effectiveness of the air-gap technique as a substitute for the grid in the pelvic examination for patient radiation dose reduction while maintaining the image quality. An anthropomorphic phantom (PBU-50) was used in this study to simulate an actual human pelvic structure. The phantom was exposed for pelvic examination using the grid and the air-gap technique to compare the exposure factors, the patient dose and the image quality produced from both methods. The patient dose was measured using a Dose Area Product (DAP) meter which was then used to estimate the gonadal dose. The images were scored by three experienced radiographers based on the Commission of European Communities (CEC) image quality criteria to determine the image quality. The result of the study indicated that the air-gap of 25 cm was the optimum air-gap distance. The gonadal dose and the effective dose were reduced from 0.130 mGy to 0.062 mGy and from 0.357 mGy to 0.172 mGy respectively when using the air-gap technique and when using the grid. The study indicated that the image quality produced by the air-gap technique was more superior to the grid. In conclusion, besides the magnification issue, the air-gap technique is suitable to be used in the pelvic radiographic examination as it reduces the patient radiation dose while improving the image quality.